Cardiovascular Outcomes of PCSK9 Inhibitors: With Special Emphasis on Its Effect beyond LDL-Cholesterol Lowering. (25th March 2018) - Bandyopadhyay, Dhrubajyoti; Ashish, Kumar; Hajra, Adrija; Qureshi, Arshna; Ghosh, Raktim K.
Abstract : PCSK9 inhibitors, monoclonal antibodies, are novel antihypercholesterolemic drugs. FDA first approved them in July 2015. PCSK9 protein (692-amino acids) was discovered in 2003. It plays a major role in LDL receptor degradation and is a prominent modulator in low-density lipoprotein cholesterol (LDL-C) metabolism. PCSK9 inhibitors are monoclonal antibodies that target PCSK9 protein in liver and inhibiting this protein leads to drastically lowering harmful LDL-C level in the bloodstream. Despite widespread use of the statin, not all the high-risk patients were able to achieve targeted level of LDL-C. Using PCSK9 inhibitors could lead to a substantial decrement in LDL-C plasma level ranging from 50% to 70%, either as a monotherapy or on top of statins. A large number of trials have shown robust reduction of LDL-C plasma level with the use of PCSK9 inhibitors as a monotherapy or in combination with statins in familial and nonfamilial forms of hypercholesterolemia. Moreover, PCSK9 inhibitors do not appear to increase the risk of hepatic and muscle-related side effects. PCSK9 inhibitors proved to be a highly potent and promising antihypercholesterolemic drug by decreasing LDL-R lysosomal degradation by PCSK9 protein. Statin drugs are known to have some pleiotropic effects. In this article, we are also focusing on the effects of PCSK9 inhibitor beyond LDL-C reduction like endothelial inflammation, atherosclerosis, its safety in patients with diabetes, obesity, and chronic kidney disease, and its influence on neurocognition and stroke.